2023
DOI: 10.1007/s00382-023-06751-5
|View full text |Cite
|
Sign up to set email alerts
|

Selecting regional climate models based on their skill could give more credible precipitation projections over the complex Southeast Asia region

Abstract: This study focuses on future seasonal changes in daily precipitation using Regional Climate Models (RCMs) from the Coordinated Regional Climate Downscaling Experiments-Southeast Asia ensemble (CORDEX-SEA). Projections using this RCM ensemble generally show a larger inter-model spread in winter than in summer, with higher significance and model agreement in summer over most land areas. We evaluate how well the RCMs simulate climatological precipitation using two skill metrics. To extract reliable projections, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…This study suggests the care of use of RCM driven by IPSL-CM5A-LR given its contrasting output compared to other models available. This finding aligns with other studies in Southeast Asia using RCMs, which reported profound bias of the downscaled IPSL-CM5A-LR due to overall model disparity from the other COR-DEX SEA simulations (Magnaye et al, 2023;Nguyen et al, 2023). In addition, other extreme indices show a relatively similar pattern of wet bias of model output.…”
Section: Rcm Evaluationsupporting
confidence: 90%
“…This study suggests the care of use of RCM driven by IPSL-CM5A-LR given its contrasting output compared to other models available. This finding aligns with other studies in Southeast Asia using RCMs, which reported profound bias of the downscaled IPSL-CM5A-LR due to overall model disparity from the other COR-DEX SEA simulations (Magnaye et al, 2023;Nguyen et al, 2023). In addition, other extreme indices show a relatively similar pattern of wet bias of model output.…”
Section: Rcm Evaluationsupporting
confidence: 90%
“…Several academic studies have utilized Regional Climate Models (RCMs) such as ICTP-RegCM4-3, MPI-CSC-REMO2009, and CCCma-CanRCM4 to analyze regional climate variations, impacts, and projections 48 , 49 . These RCMs are regarded as valuable tools for downscaling global climate model outputs to provide more detailed climate information at regional and local levels.…”
Section: Methodsmentioning
confidence: 99%